56.7k views
1 vote
Heeeeeeeeeeeeeeeeeeeeeeeeeeelllllllllllllllllllpppppppppppppppppp

Heeeeeeeeeeeeeeeeeeeeeeeeeeelllllllllllllllllllpppppppppppppppppp-example-1

1 Answer

6 votes

Answer:

x = 5

Explanation:


6 - 2x = 5x - 9x + 16

Simplify

That's


6 - 2x = - 4x + 16

Add 4x to both sides of the equation


6 - 2x + 4x = 4x - 4x + 16 \\ 6 + 2x = 16

Subtract 6 from both sides of the equation


6 - 6 + 2x = 16 - 6 \\ 2x = 10

Divide both sides by 2


(2x)/(2) = (10)/(2) \\

We have the final answer as

x = 5

Hope this helps you

User Dhke
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.